2016
DOI: 10.1038/srep38562
|View full text |Cite
|
Sign up to set email alerts
|

Artificial high birefringence in all-dielectric gradient grating for broadband terahertz waves

Abstract: Subwavelength dielectric gratings are widely applied in the phase and polarization manipulation of light. However, the dispersion of the normal dielectric gratings is not flat while their birefringences are not enough in the THz regime. In this paper, we have fabricated two all-dielectric gratings with gradient grids in the THz regime, of which artificial birefringence is much larger than that of the equal-grid dielectric grating demonstrated by both experiments and simulations. The transmission and dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Metamaterials, which are artificial materials composed of subwavelength elements [17][18][19][20][21], can be flexibly designed to achieve various unusual functions that cannot be fulfilled with traditional materials and are often used to design functional devices required for THz waves. Many THz polarization convertors based on metamaterials are designed to replace traditional waveplates [22][23][24][25][26][27][28][29][30][31][32]. Grady et al demonstrated metamaterial-based THz polarization converters capable of rotating a linear polarization state into its orthogonal one [22].…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials, which are artificial materials composed of subwavelength elements [17][18][19][20][21], can be flexibly designed to achieve various unusual functions that cannot be fulfilled with traditional materials and are often used to design functional devices required for THz waves. Many THz polarization convertors based on metamaterials are designed to replace traditional waveplates [22][23][24][25][26][27][28][29][30][31][32]. Grady et al demonstrated metamaterial-based THz polarization converters capable of rotating a linear polarization state into its orthogonal one [22].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the structure is based on our previous work, where we demonstrated that Mie or WGM resonances can be excited in a sub-wavelength fiber with a relatively medium refractive index using point source excitation, leading to an enhanced magnetic response in THz frequency range [26]- [28], [48]. It should be noted that in this work we concentrate on frequency range (0.1 − 0.6 THz) where the structure is operating in metasurface [49], [50] and not grating [51], [52] regime. This single-layer metasurface can operate in both reflection and transmission modes, which opens new opportunities to develop single-layer THz devices for wave front engineering.…”
Section: Introductionmentioning
confidence: 99%
“…All-dielectric meta-devices and gradient grating polarization converters, proposed by Chen et al and Kruk et al, have shown remarkable efficiencies ∼ 99 % [ 26 , 27 ]. The structures exhibit high birefringence ratios, 0.35 and 0.9, in the terahertz and near-infrared regions, respectively.…”
Section: Introductionmentioning
confidence: 99%